Analysis of the Cross-Wire Welding Process Stability - Čabrijan, Ivan; Vrtovšnik, Domagoj; Vlatković, Maja; Pavletić, Duško (Tehnički glasnik, 2022)
The research paper was prepared within the framework of a project whose aim is to improve the durability of the corrosion protection properties of the product by regulating the input parameters of the cross-wire welding process. Cross-wire welding is a subtype of electric resistance welding. Products made by the cross-wire welding process are widely used in everyday life and can be found in the form of grids, gratings, fencing systems, baskets, guards, etc. The subject of the research work is a preliminary analysis of the stability of the cross-wire welding process. The results of the performed analysis will serve as a starting point for the second phase of the project. Since the recorded values of the set down output parameter differ significantly from the expected values, this parameter is considered as an indicator of the process stability. From the specific trend of the results in the performed analysis, it was concluded that the position of the electrode has a significant influence on the result, which was confirmed by comparing the test results before and after the preliminary tests.